2008
DOI: 10.3386/w14132
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Economic Growth: Evidence from the Last Half Century

Abstract: for helpful comments and suggestions. The views expressed herein are those of the author(s) and do not necessarily reflect the views of the National Bureau of Economic Research. NBER working papers are circulated for discussion and comment purposes. They have not been peerreviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
158
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(187 citation statements)
references
References 37 publications
10
158
2
7
Order By: Relevance
“…On the other hand, if the two effects are opposite, the direct effect would prevail at first, then the capital accumulation will eventually drive the economic growth, possibly inverting the sign of the total effects. Dell et al (2008) find evidence that changes in temperature have a long lasting impact on economic growth, particularly for poor countries, but do not provide a convincing explanation for this effect. 7 In the ICES model, instead, we are able to analyze how the various climate change impacts may affect the capital rate of return, thereby influencing the allocation of international investments.…”
Section: The Ices Modelmentioning
confidence: 85%
“…On the other hand, if the two effects are opposite, the direct effect would prevail at first, then the capital accumulation will eventually drive the economic growth, possibly inverting the sign of the total effects. Dell et al (2008) find evidence that changes in temperature have a long lasting impact on economic growth, particularly for poor countries, but do not provide a convincing explanation for this effect. 7 In the ICES model, instead, we are able to analyze how the various climate change impacts may affect the capital rate of return, thereby influencing the allocation of international investments.…”
Section: The Ices Modelmentioning
confidence: 85%
“…Using historical data on temperatures and precipitation over the past 50 years for a panel of 136 countries, Dell, Jones, and Olken (2008) have shown that higher temperatures reduce GDP growth rates but not levels. The impact they estimate is large -a decrease of 1.1 percentage points of growth for each 1 • C rise in temperature -but significant only for poorer countries.…”
Section: Economic Impactmentioning
confidence: 99%
“…It remains however, that in spite of their very wide use in the CC impact literature, IAMs are based on aggregation of effects on selected subsets of sectors and impact mechanisms separately measured under a host of strong assumptions (Stern, 2007, Dell et al, 2008.…”
Section: Total Impact Assessment Modelsmentioning
confidence: 99%
“…To address this shortcoming of adding up effects of separately specified impact pathways, Dell et al (2008) analyzed effects of annual variations of rainfall and temperature on aggregate growth indicators for countries across the world. This approach avoids the need to make assumptions about what impact mechanisms to include and how they interact to generate aggregate impacts.…”
Section: Total Impact Assessment Modelsmentioning
confidence: 99%
See 1 more Smart Citation